THE trade SHOW OF SHOWS. - Devoss, David; Sander, Eric (Smithsonian, 2001)
Focuses on the events and significance of Comdex, an international information technology trade show held in Las Vegas, Nevada. Chronology of events and activities at Comdex over three days, including an address by Microsoft Corp. chief executive officer Bill Gates; Costs of exhibiting; Reasons for the popularity of the show within the industry; Social gatherings in Las Vegas related to the trade show; Benefits of attending a Comdex.